Thunderclap Headache without Subarachnoid Hemorrhage Associated with Regrowth of Previously Coil-Occluded Aneurysms - Byrum, E.P.; McGregor, J.M.; Christoforidis, G.A. (American Journal of Neuroradiology, 2009)
SUMMARY: Thunderclap headache is a sudden, high-intensity headache often associated with subarachnoid hemorrhage secondary to a ruptured intracerebral aneurysm. A variety of less common causes have now been described. This report presents the cases of 2 patients who experienced thunderclap headache after regrowth of an aneurysm, without hemorrhage of previously coiled aneurysms. Thunderclap headache after endovascular occlusion of a ruptured intracranial aneurysm may be a symptom of aneurysm regrowth and may warrant angiographic investigation.